Multiple functionally divergent and conserved copies of alpha tubulin in bdelloid rotifers - Eyres, Isobel; Frangedakis, Eftychios; Fontaneto, Diego; Herniou, Elisabeth; Boschetti, Chiara; Carr, Adrian; Micklem Gos, Gos; Tunnacliffe, A.; Barraclough, Timothy (BMC Evolutionary Biology, 2012)
International audience Bdelloid rotifers are microscopic animals that have apparently survived without sex for millions of years and are able to survive desiccation at all life stages through a process called anhydrobiosis. Both of these characteristics are believed to have played a role in shaping several unusual features of bdelloid genomes discovered in recent years. Studies into the impact of asexuality and anhydrobiosis on bdelloid genomes have focused on understanding gene copy number. Here we investigate copy number and sequence divergence in alpha tubulin. Alpha tubulin is conserved and normally present in low copy numbers in animals, but multiplication of alpha tubulin copies has occurred in animals adapted to extreme environments, such as cold-adapted Antarctic fish. Using cloning and sequencing we compared alpha tubulin copy variation in four species of bdelloid rotifers and four species of monogonont rotifers, which are facultatively sexual and cannot survive desiccation as adults. Results were verified using transcriptome data from one bdelloid species, Adineta ricciae.